A Feasibility study on E3 wood products - Bernardo, Maruh Michelle; Ortiz, Frances Sophia; Portus, Alyssa Jean.; Urbano, Miguel Andro (Diliman, Quezon City College of Engineering, 1987)
This paper tackles the market, technical, financial, and socio-economic feasibility of E3 Wood Products, composed of E3 Plywood and E3 Particle Board that uses recycled waste plastics as binder component. The study was conducted because an increasing demand for plywood and particle board was identified using information from the National Statistics Office and through thorough research and interviews with the Philippine Wood Producers Association, it was discovered that this new technology enables certain characteristics that are sought by the market: it is Economical, Environmental, and Emission-free. Upon careful analysis and evaluations, it was determined that the product is feasible in all four aspects within the five-year study period. The first step taken was to identify the market and create strategies to convince the market to use the E3 products. Through market analysis, it was identified that the target market of E3 Wood Products is the business market, composed of wholesalers, retailers, and contractors who, in turn, cater the ultimate end user: the current 83,115 private residential construction projects in the country. By proving that there is a gap between the demand and supply for these wood products, a sales forecast was created, which is an integral component in the Technical study. To strategically market these products, the 4Ps (Position, Price, Placement, and Promotions) were used to create the framework in marketing the products effectively to its target market. It then resulted to the projected sales and marketing budget. The next step is to identify whether the product is feasible to produce given the sales forecast generated from the market study and to estimate the costs associated with starting up and sustaining the business. Through research and systemic evaluation, potential suppliers for raw materials and production equipment were chosen among a pool of options. Using the five year sales forecast from the Marketing study, computations were conducted which yielded the number of equipment needed to sustain the operations. This information was further used to come up with the production plan, manpower plan, and utilities plan that are recommended to the company in its first five years of operations. In addition, an organizational structure that could cater the needs of the business was also recommended. But the most important output of this part were the costs associated in start-up, investment, and operation, which costs Php 46,790,601.21. Thirdly, using the costs generated from the Technical study, financial analysis was conducted to check the availability of financial resources and to identify the proper allocation of these resources to ensure the smooth flow of operations. These costs as well as the projected revenues were used to compute for different financial ratios to determine the profitability of the business, which can be used to seek out potential investors. After analysing these ratios, it was determined that the business exhibits profitability (through EPS and RoE), solvency (through the Quick ratio), and a promising market (given the increasing demand). Lastly, a Socio-Economic study was conducted to determine the impact that the business could bring to different stakeholders. This impact was identified to be beneficial, in the form of economic, environmental,and health benefits.
Feasibility study
Typescript
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: E3 Wood Products; Participatory monitoring and evaluation (Project management); Plywood industry; Particle board industry